Bioethics and rural health: theorizing place, space, and subjects - Kelly, Susan E (Social science & medicine (1982), 2003)
The field of bioethics has been criticized for its universalizing tendencies, attributed in a large part to its foundations in moral philosophy and the level of abstraction of much bioethical discourse. Efforts to particularize bioethics have included the “turn toward casuistry”, the emergence of feminist and disability rights critiques of mainstream bioethics, and ethnographic contributions that examine the situatedness of ethical acts, practices, and meanings in local contexts. Such work introduces into bioethics dimensions of space, place, and time; nonetheless, these remain relatively unexplored as constitutive elements and/or influences of the phenomena of ethics discourse and ethics-related practices. Drawing from an ethnographic study of genetics in rural health, this paper presents a sociological discussion of space/time and bioethics through examination of rural health settings. Issues raised include intersections of spatial and power relations, socio-spatial gradients of expertise, and socio-spatial dimensions of ethics knowledge and practices within medical settings.